1996
DOI: 10.1111/j.1365-2915.1996.tb00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation in screwworm

Abstract: . Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis was used to characterize mitochondrial DNA (mtDNA) variation in screwworms, Cochliomyia hominivorax, and secondary screwworm, C. macellaria, from the Caribbean, North America and South America . Four amplicons, totaling 7 .1 kb, were analysed with sixteen restriction enzymes . A total of 133 restriction sites was observed in the two species, 104 in C. hominivorax, of which nineteen were variable, and ninetyfive in C. macel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
4
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
0
15
4
2
Order By: Relevance
“…This finding was also indicated in the dendrogram generated from data of RAPDs using the primers for identifying screwworms from other species. These results differ somewhat from the conclusions made by Taylor et al (1996), who divided C. hominivorax populations into 3 assemblages (North and Central America, South America, and Jamaica) but were using RFLP of mtDNA and had fewer samples and fewer bands for analysis.…”
Section: Discussioncontrasting
confidence: 56%
“…This finding was also indicated in the dendrogram generated from data of RAPDs using the primers for identifying screwworms from other species. These results differ somewhat from the conclusions made by Taylor et al (1996), who divided C. hominivorax populations into 3 assemblages (North and Central America, South America, and Jamaica) but were using RFLP of mtDNA and had fewer samples and fewer bands for analysis.…”
Section: Discussioncontrasting
confidence: 56%
“…Within Panama, Cochliomyia macellaria is the most closely related species of Calliphorid. This species is broadly sympatric with C. hominivorax across Central and South America [16, 17]. Although the two species have not been reported to hybridize in the wild and previous studies showed that they mate very rarely in caged settings, producing no hybrid offspring [18, 19], we studied the potential for transgenic C. hominivorax males to mate with wild type C. macellaria females in the laboratory.…”
Section: Resultsmentioning
confidence: 99%
“…Flies from Jamaica may also be distinct, but support for this is less clear鈥恈ut. Previous molecular studies on flies from this region support the suggestion that C. hominivorax from Jamaica may be genetically distinct (Taylor et al , 1996).…”
Section: Discussionmentioning
confidence: 67%